Compensatory Function of the Subtalar Joint for Lower Extremity Malalignment - Kensei Yoshimoto; Masahiko Noguchi; Akifumi Yamada; Yuki Nasu (Advances in Orthopedics, 2019)
It is important to evaluate the subtalar joint and hip-knee-ankle alignment to understand lower extremity alignment. In this review, we focused on the compensatory changes in the subtalar joint alignment for the deformity of the knee and ankle joint, reviewing previous research. The subtalar joint alignment was compensatory valgus in patients with varus knee and ankle deformity, whereas it was uncertain whether the subtalar joint alignment was compensatory varus in patients with valgus knee and ankle deformity. The subtalar joint valgus alignment improved after total knee arthroplasty or high tibial osteotomy for varus knee deformity, even if the deformity was severe. In contrast, whether the subtalar joint alignment changed after the surgery for ankle or valgus knee deformity has not been considered. Further research on the compensatory function of the subtalar joint is needed.